A magnetic field induced undulated surface and the shift of the active/passivation transition threshold of iron in a sulfuric acid solution. (December 2017) - Li, Hongjuan; Xiong, Qi; Lu, Zhanpeng; Chen, Junjie; Xiao, Qian; Ru, Xiangkun; Lin, Sichun; Ma, Jiarong; Chen, Zhen
Highlights: A magnetic field induced an irreversible state of iron in a sulfuric acid solution. Undulated surface after anodic dissolution was formed under the magnetic field. Irregular dissolution caused by uneven distribution of induced magnetic field. Passivation potential decreased by higher scan rate at 0.4 T but insensitive at 0 T. Magnetic field modulated reaction rate and surface affected passivation potential. Abstract: An unevenly distributed magnetic field caused irreversible electrochemical states of iron in a sulfuric acid solution due to the undulated surface generated by anodic dissolution. The magnetic field affected the activation-passivation transition threshold by modifying the interface reaction rate and surface morphology. The passivation onset potential was increased by decreasing the scan rate under 0.4 T, and was insensitive to the scan rate at 0 T.